Effects of Bacillus subtilis on growth performance and intestinal flora of Penaeus vannamei - Hongzhen Cao; Duanduan Chen; Leifeng Guo; Rong Jv; Yunteng Xin; Wei Mo; Chen Wang; Pengfei Li; Hui Wang (Aquaculture Reports, 2022)
In this article,It is of great significance to reduce the use of antibiotics and improve the efficiency of aquaculture. With companion feeding, Penaeus vannamei was fed with different concentrations of Bacillus subtilis. After feeding for 30 days, we weighed them to detect their growth performance, took hepatopancreas and blood samples to measure alanine aminotransferase, aspartate aminotransferase α-amylase, phenol oxidase, superoxide dismutase and peroxidase, and the content of crude protein in muscle tissue were measured. The result showed that adding 0.5% of B. subtilis to the feed has the best effect. When analyzing the intestinal flora, we found that the Proteobacteria and Firmicutes as the dominant phyla have significant differences compared with the control group. According to the Shannon diversity index, it can be seen that as the concentration of probiotics increases, the abundance of intestinal flora also tends to increase. According to different UPDMA cluster branches, it can be seen that there may be an enrichment of the same genus among groups. When the concentration of probiotics is 1%, the concentration of probiotics has a greater impact on the function of the intestinal flora.